2019
DOI: 10.1002/ajmg.a.61284
|View full text |Cite
|
Sign up to set email alerts
|

Study of carrier frequency of Warsaw breakage syndrome in the Ashkenazi Jewish population and presentation of two cases

Abstract: Warsaw breakage syndrome (WABS), caused by bi-allelic variants in the DDX11 gene, is a rare cohesinopathy characterized by pre-and postnatal growth retardation, microcephaly, intellectual disability, facial dysmorphia, and sensorineural hearing loss due to cochlear hypoplasia. The DDX11 gene codes for an iron-sulfur DNA helicase in the Superfamily 2 helicases and plays an important role in genomic stability and maintenance. Fourteen individuals with WABS have been previously reported in the medical literature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
2
12
0
6
Order By: Relevance
“… Variant 1 Variant 2 DNA Protein DNA Protein v.d. Lelij et al 1 WABS01 c.2271+2T>C p.C754P fs*9 c.2689-2691del p.K897del Capo-Chichi et al 6 3 patients c.788G>A p.R263Q c.788G>A p.R263Q Bailey et al 5 1 patient c.638+1G>A splice site c.1888delC p.R630F fs*23 Eppley et al 7 2 patients c.1523T>G p.L508R c.1949-1G>A splice site Alkhunazi et al 4 Patient 1 c.606delC p.Y202* c.2372G>A p.R791Q Patient 2 c.1133G>C p.R378P c.1133G>C p.R378P Patient 3+4 c.2576T>G p.V859G c.2576T>G p.V859G Patient 5 c.2638dupG p.A880G fs*94 c.2638dupG p.A880G fs*94 Bottega et al 8 2 patients c.2507T>C p.L836P c.907-920del p.K303E fs*22 Rabin et al 9 2 patients c.1763-1G>C splice site c.1763-1G>C splice site Present study WABS02 c.169G>C p.G57R c.2692-1G>A p.K897_F898ins25 WABS03 c.1403dupT p.S469V fs*31 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Variant 1 Variant 2 DNA Protein DNA Protein v.d. Lelij et al 1 WABS01 c.2271+2T>C p.C754P fs*9 c.2689-2691del p.K897del Capo-Chichi et al 6 3 patients c.788G>A p.R263Q c.788G>A p.R263Q Bailey et al 5 1 patient c.638+1G>A splice site c.1888delC p.R630F fs*23 Eppley et al 7 2 patients c.1523T>G p.L508R c.1949-1G>A splice site Alkhunazi et al 4 Patient 1 c.606delC p.Y202* c.2372G>A p.R791Q Patient 2 c.1133G>C p.R378P c.1133G>C p.R378P Patient 3+4 c.2576T>G p.V859G c.2576T>G p.V859G Patient 5 c.2638dupG p.A880G fs*94 c.2638dupG p.A880G fs*94 Bottega et al 8 2 patients c.2507T>C p.L836P c.907-920del p.K303E fs*22 Rabin et al 9 2 patients c.1763-1G>C splice site c.1763-1G>C splice site Present study WABS02 c.169G>C p.G57R c.2692-1G>A p.K897_F898ins25 WABS03 c.1403dupT p.S469V fs*31 …”
Section: Resultsmentioning
confidence: 99%
“…The oldest WABS patient reported, WABS04, died at the age of 64 with no evidence of cancer. The clinical spectrum of WABS is heterogeneous and also shows considerable overlap with the cohesinopathies Roberts Syndrome (RBS) and Cornelia de Lange Syndrome (CdLS), with the most notable exceptions being limb reductions, which are not found in WABS (although clinodactyly is observed), and abnormal skin pigmentation including café-au-lait spots, which are not found in RBS and CdLS 1,[4][5][6][7][8][9] . WABS has been classified as a cohesinopathy because of the spontaneous railroad chromosomes and PCS that are observed in metaphase spreads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last report of WABS describes two novel unrelated patients of Ashkenazi Jewish descent, both homozygous for the same DDX11 variant (c.1763-1G>C) 35. RNA sequencing analyses revealed that this mutation caused altered messenger RNA splicing giving rise to a frame-shift of the DDX11 open reading frame with production of an abnormal protein.…”
Section: History Of Wabs Clinical Reportsmentioning
confidence: 99%
“…Therefore, in order to avoid mistakes in diagnosis, clinicians are advised to analyze metaphase chromosome spreads for spontaneously occurring morphological anomalies (PCD and PCS), which are typically found in WABS- and RBS-affected individuals and not in FA or CdLS patients 28Table 1Most Common Clinical Features Observed in WABS PatientsReferencePhenotypevan der Lelij et al (2010)24 (N = 1)Capo-Chichi et al (2013)29 (N = 3)Bayley et al (2015)30 (N =1)Eppley et al (2017)31 (N = 2)Alkhunaizi et al (2018)32 (N = 5)Bottega et al (2019)34(N = 2)Rabin et al (2019)35 (N = 2)Number of Patients (N = 16)Sex1 M1 M2 F1 F2 F4 M1 F2 F1 M1 F7 M9 FIntra-uterine growth restriction+ (1/1)+ (2/2)+ (1/1)+ (2/2)+ (5/5)+ (2/2)+ (1) NA (1)+ (15/16) NA (1)Post-natal growth retardation+ (1/1)+ (2/2)+ (1/1)+ (2/2)+ (5/5)+ (2/2)+ (2/2)+ (16/16)Microcephaly+ (1/1)+ (2/2)+ (1/1)+ (2/2)+ (5/5)+ (2/2)+ (2/2)+ (16/16)Intellectual disability+ (1/1)+ (2/2)+ (1/1)+ (2/2)+ (5/5)+ (1) − (1)+ (2/2)+ (15/16) − (1/16)Facial dysmorphia+ (1/1)+ (2/2)+ (1/1)+ (2/2)+ (5/5)…”
Section: Diagnostic Overlap Between Wabs and Fanconi Anemiamentioning
confidence: 99%